Inovasi dalam Manajemen Pendidikan: Strategi untuk Meningkatkan Kualitas Sekolah - Ilhami Ilhami; Alam Samudra; Binti Arifah Nurhasanah; M Taufik Jhauzal (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
This article explores innovation strategies in educational management to enhance school quality in the digital era. The study employs a literature review method by analyzing various relevant references. The findings reveal that educational innovation, whether through top-down or bottom-up approaches, plays a significant role in modernizing educational systems. Implementing innovation requires integrated management support, including continuous planning, execution, evaluation, and refinement. Innovation strategies involving stakeholder collaboration, technological utilization, and adherence to National Education Standards have been shown to effectively improve education quality. However, challenges such as resistance to change, resource limitations, and systemic barriers must be addressed with a comprehensive approach. This article highlights the importance of sustainable and integrated innovation to meet future educational needs.